Finite Element Analysis of Concrete Slabs Under Torsion - Ghassan M. Werdina; Aziz, Omar Q. (Zanco Journal of Pure and Applied Sciences, 2025)
Many researchers have been interested in the study of torsion in concrete members during the last decades. Most of these studies focused on the reinforced beams under torsion and not deeply researched the case of slab. This paper presents a study on the behavior of reinforced concrete slabs under torsion by using finite element analysis (FEA). Twenty-one slabs with different reinforcement and concrete compressive strength have been included in the study. To apply torsional moment on the slabs, vertical displacement at three corners was constrained and the load was applied to the fourth corner. According to the results, steel bar size had more influence on the torsional yielding moment compared to the torsional cracking moment. Using steel bar size of 12 mm instead of 8 mm increased the torsional cracking and yielding moments by 4% and 19% respectively, for the slab with compressive strength of concrete of 50 MPa. Furthermore, both the torsional cracking and yielding moments substantially increased with the increase in compressive strength of concrete. Raising the compressive strength of concrete from 21 MPa to 50 MPa increased the torsional cracking and yielding moments by 54% and 44% respectively. Torsional stiffness of reinforced concrete slabs in the uncracked stage is about 20-28 times that in the cracked stage.